2011
DOI: 10.2967/jnumed.110.082875
|View full text |Cite
|
Sign up to set email alerts
|

Examination of 11C-Methionine Metabolism by the Standardized Uptake Value in the Normal Brain of Children

Abstract: The aim of this study was to determine the uptake of L-[methyl-11 C]-methionine ( 11 C-MET) in the normal brain of patients younger than 20 y, to facilitate more accurate diagnoses in young patients. Methods: Eighty-two patients were categorized into 4 groups according to their age. They underwent 11 C-MET PET, and a standardized uptake value (SUV) was determined for different brain regions including the frontal lobe, parietal lobe, cerebellum, and brain stem. Results: Compared with all other parts of the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The highest uptake was found in the cerebellum and occipital cortex, with less in white matter. The study of Nagata also showed high uptake in the cerebellum of normal children and increasing SUV in the frontal lobes and cerebellum with age (27). …”
Section: Discussionmentioning
confidence: 93%
“…The highest uptake was found in the cerebellum and occipital cortex, with less in white matter. The study of Nagata also showed high uptake in the cerebellum of normal children and increasing SUV in the frontal lobes and cerebellum with age (27). …”
Section: Discussionmentioning
confidence: 93%
“…Magnetic resonance imaging (MRI) should precede 11 C-Met PET to check the morphological anatomy of the central nervous system (CNS). The effect of aging on physiological uptake in the brain is limited, although SUV in the normal brains of children is slightly different from that in the normal brains of adults ( 4 ). Whether or not the patients should be in the fasting state before 11 C-Met PET is also controversial.…”
Section: Physiological Uptake and Normal Variantsmentioning
confidence: 96%
“…Moreover, methionine metabolism may vary with growth stage of life-cycle. Nagata et al [ 11 ] reported that the uptake of methionine in the brain of children gradually increased with age. In rat, activity of liver γ-cystathionase, a key enzyme for the transsulfuration of methionine, was lower in newborns than in adults [ 12 ].…”
Section: Introductionmentioning
confidence: 99%